Experimental evaluation of a diesel engine with diesel oil and fish oil blends. - Valderrama Romero, Andres (1998)
It is proposed to use fish oil mixed with Diesel 2 oil in diesel engines, by adding it in volumetric proportion to the amount of diesel fuel. This mixture is used as an alternative fuel to reduce diesel fuel consumption; its use is low cost, which makes it feasible and convenient for use in diesel engines of small and medium power fishing boats. The tests were carried out at the National University of Engineering in an experimental single-cylinder engine and demonstrate the possibility of partially replacing Diesel 2 oil with fish oil. Translated with www.DeepL.com/Translator (free version)